The Evolvement & Use of Non-Electric Blasting Techniques at the Kidd Creek Mine - P N. Blakey (International Society of Explosives Engineers, 1978)
The base metal orebody of Texasgulf Canada Ltd. was mined initially by open pit. Conventional mining techniques were followed underground, but experimentation showed that open pit methods of drilling and blasting could be adapted. This paper deals with the consequent development of blasting techniques to suit underground stope design and damage criteria, in a large tonnage operation.